PENGEMBANGAN MEDIA PEMBELAJARAN ANIMASI SUBMIKROSKOPIK BERBASIS FLASH PADA MATERI KESETIMBANGAN KIMIA - Toni, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractLearning media animation could demonstrate the abstract of the subject material to facilitate students in understanding the material. The purpose of this research was to describe feasibility of flash-based animation submicroscopic learning media and the teachers and students response towards the media. The research method used was research and development (R&D) which consists of four stages namely, (1) designing (2) writing script, (3) production and (4) evaluation of the media. Evaluation of the media consisted of 3 steps, namely, (1) one to one evaluation (2) small group evaluation, and (3) field evaluation. Learning media assessed via questionnaire. During one to one evaluation, material and media experts were in charge at evaluation. According to media and matter experts, the media was valid, so that the media could be used in learning. During small group and field group evaluation, teacher and student have responded to the media. Based on result small group and field group evaluation, this media could be used in learning as well. Key words: development, submicroscopic, animation, flash, media